SECURITY SISTEM PADA BRANKAS DENGAN KARTU E-KTP DAN PASSWORD BERBASIS GERBANG LOGIKA MENGGUNAKAN KOMBINASI IC TTL - Muarif, Muarif; Mardiansyah, Mardiansyah; Romdhoni, Romdhoni (Universitas Sangga Buana, 2024)
A safe is designed to securely store valuable items, including important documents, jewelry, money, and other precious belongings. Modern safes often feature manual or semi-automatic locking systems, such as combination locks or cylinder locks. However, combination locks can be less secure and efficient, making them vulnerable to theft. In Indonesia, the adoption of RFID (Radio Frequency Identification) technology, especially in E-KTP cards, has seen progress, though its potential remains underutilized. This research integrates an advanced logic gate circuit using IC gates—AND, XOR, and NOT—functioning as a password mechanism. The device operates by requiring users to tap their E-KTP against a reader to unlock the safe door. Upon a successful tap, an LCD screen displays relevant information and requests a 16-bit binary password made up of 8